2018
DOI: 10.1016/j.ygyno.2018.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing inter-component heterogeneity of biphasic uterine carcinosarcomas

Abstract: From DNA analysis, our results indicate a monoclonal disease origin for this cohort. Yet expression-derived EMT statuses of the carcinomatous and sarcomatous components were often discrepant, and advanced cases displayed greater genomic heterogeneity. Therefore, separately-profiled components of UCS tumors may better inform disease progression or potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We have previously suggested that EMT is activated in ECS [65,73,84,85]. Further studies have confirmed this suggestion [25,38,39,84,86]. For example, we used real-time PCR to measure the differences in the expression of, E-cadherin, cadherin-11, SPARC, SNAIL , ZEB1 , ZEB2 , TWIST-1 , TCF4 , TGFβ1, and TGFβ2 between the epithelial and mesenchymal components of 23 ECSs.…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have previously suggested that EMT is activated in ECS [65,73,84,85]. Further studies have confirmed this suggestion [25,38,39,84,86]. For example, we used real-time PCR to measure the differences in the expression of, E-cadherin, cadherin-11, SPARC, SNAIL , ZEB1 , ZEB2 , TWIST-1 , TCF4 , TGFβ1, and TGFβ2 between the epithelial and mesenchymal components of 23 ECSs.…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 84%
“…Previous studies combining aberrant expression of p53 and mutational analysis estimated a TP53 mutation prevalence of 50–60% [3,12,22,27,32,33,34,35]. However, subsequent studies using Next Generation Sequencing (NGS) techniques have shown that the true frequency of TP53 mutation in ECS is very high, between 64% and 91% [29,30,36,37,38,39,40]. In effect, TP53 mutations are the most frequent molecular alterations in ECS (Table 1).…”
Section: Serous-like Molecular Alterations In Ecsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best reference for the genomic alterations in solid tumors is the normal tissue adjacent to the cancer nodule as it became standard in several laboratories[ 46 - 49 ]. We used such reference when profiling surgically removed tumors from persons affected by clear cell renal cell carcinoma[ 7 ], papillary thyroid cancer[ 8 ] and prostate cancer[ 10 ].…”
Section: Cancer Samplesmentioning
confidence: 99%
“…For example, UCS shares epidemiologic features and patterns of chromosomal instability with high-grade carcinomas, and also shares mutational spectra with ECs, including frequent mutations in loci encoding PI3K pathway components (68). Comparison of microdissected epithelial and mesenchymal components from individual patients has revealed common chromosomal alterations and mutations, arguing for a monoclonal origin (911). Systematic genomic characterizations of UCS have identified frequent mutations in some genes, most notably Tp53 , but such mutations also frequently occur in serous and high-grade endometrioid cancers and are not specific to UCS (6).…”
mentioning
confidence: 99%